Shakespeare survey. - Nicoll, Allardyce, 1894-1976.; Muir, Kenneth (Cambridge [England] ; New York : Cambridge University Press, 1948)
"An annual survey of Shakespearian study and production."
Editor: v. 1-18, Allardyce Nicoll ; v. 19, Kenneth Muir
Some volumes bear also distinctive titles.
"Issued under the sponsorship of the University of Birmingham, the Shakespeare Memorial Theatre, the Shakespeare Birthplace Trust," 1948-1965.
Vols. 1-10 (1948-1957), in v. 11; Vols. 11-20 (1958-1967), in v. 21; Vols. 21-30 (1968-1977), in v. 31; Vols. 31-40 (1978-1987), in v. 41; Vols. 41-50 (1988-1997), in v. 51; Vols. 1-60 (1948-2007). 1 v.
Keywords: d